KAJIAN ESTETIKA PERUPA MUDA LUKISAN RIDHA NURSAFITRI BERJUDUL: HEDONISME DALAM PANDANGAN HIDUP MINANGKABAU - Vidella Miranda Lestamega (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
In this modern era, everyday human life is interfered with and filled with programs of technological progress and entertainment, which can change people's perspective on life with the introduction of more modern foreign culture. From this, Ridha Nursafitri as a Fine Arts student who cares about her culture (Minangkabau) chose to visualize phenomena that are happening in her environment into a painting because this is considered an interesting issue to be used as a reminder for the community packaged in the form of a work of art. visual. This becomes interesting to research based on the rare idea of art lovers who examine the meaning of paintings that relate to culture and social environmental phenomena in society. The purpose of this painting is to educate the Minangkabau people regarding awareness in responding to the current era regarding traditional Minangkabau culture which is starting to be abandoned and is in danger of being replaced by a more modern culture. This research uses a qualitative approach with descriptive research type. The subject used in this research is a painting by a young artist Ridha Nur Safitri, S.Pd. entitled